(untitled) (Journal of Dhaka Medical College, 2024)
Introduction: Dyspepsia is a fairly common group of symptoms including epigastric pain, epigastric burning, postprandial fullness, early satiation, bloating in the upper abdomen, nausea, vomiting and belching. Interestingly the majority of them are found to have no ulcer, and they are termed as non-ulcer dyspepsia (NUD). However. Different studies worldwide have found there is an association between H. Pylori infection and NUD. Objective: To evaluate the infection rates of H. pylori in patients, presenting with dyspepsia without any evidence of ulcer on endoscopy. Materials and methods: This cross-sectional study was conducted from June, 2022 to December, 2022. The study included 100 patients (46 males and 54 females) with NUD and recruited by convenient sampling method. Result: In the study, the prevalence of H. pylori infection in patients with NUD is 53% on the basis of (Rapid urease test) RUT. Gender-based prevalence was found to be 53.7% and 52.17% for women and men, respectively. The highest prevalence rate was found in the age group of 25-34 years. The prevalence of H. pylori infection was slightly higher for urban people. Conclusion: H.Pylori infection can be easily identified by RUT. The study has found significant correlation of H. pylori infection with NUD by using RUT. J Dhaka Med Coll. 2023; 32(1) : 4-8